The Best of Times and the Worst of Times: Polarization and Presidential Success in Congress. Issue 3 (1st September 2016) - Franklin, Daniel Paul; Fix, Michael P.
Abstract : For better or for worse, presidents receive much of the credit and much of the blame for their legislative success in Congress. Indeed, much has been written about the correlates of presidential success in Congress. In this article, we test the proposition that presidential success in Congress is mainly a function of context and the context of presidential interactions with Congress has changed over the past 50 years. Specifically, it is both the best of times and worst of times for presidential relations with the legislative branch. It is increasingly the case that because of partisan polarization in Washington, presidents can be quite successful, if they command a majority. However, if they face a divided government gridlock is the result and overcoming that gridlock has gotten to be more difficult over time.